2022
DOI: 10.3390/rs14081852
|View full text |Cite
|
Sign up to set email alerts
|

Design of an FPGA-Based High-Quality Real-Time Autonomous Dehazing System

Abstract: Image dehazing, as a common solution to weather-related degradation, holds great promise for photography, computer vision, and remote sensing applications. Diverse approaches have been proposed throughout decades of development, and deep-learning-based methods are currently predominant. Despite excellent performance, such computationally intensive methods as these recent advances amount to overkill, because image dehazing is solely a preprocessing step. In this paper, we utilize an autonomous image dehazing al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…12 that the results of Liu et al 12 and Upadhyay and Sarawadekar 13 are darker, such as the wall of the classroom image. Similarly, the results of Tan et al 14 and Lee et al 16 are also suffering from over-enhancement. Our results have more balanced colors and sharp object details overall, whereas the performance on FPGA is similar to that on PC.…”
Section: Synthetic Image Testsmentioning
confidence: 78%
See 3 more Smart Citations
“…12 that the results of Liu et al 12 and Upadhyay and Sarawadekar 13 are darker, such as the wall of the classroom image. Similarly, the results of Tan et al 14 and Lee et al 16 are also suffering from over-enhancement. Our results have more balanced colors and sharp object details overall, whereas the performance on FPGA is similar to that on PC.…”
Section: Synthetic Image Testsmentioning
confidence: 78%
“…Tan et al 14 also have color distortion in the sky area, and the brightness of some object areas is dark after defogging. When the fog is not very large, Lee et al 16 will cause excessive fog removal, resulting in oversaturated colors. Our defogging approach can get adequate satisfactory defogging results in most cases, even in sky scenes or places where the depth changes abruptly.…”
Section: Experimental Results and Comparisonmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, spaceborne remote sensing platforms not only perform CNN-based image processing, but also perform image preprocessing, such as radiation correction and image dehazing, to improve the performance of CNN-based image processing [24]. Some FPGA-based studies showed that image preprocessing requires a lot of hardware resources to implement [25,26]. For example, Qi et al [25] implemented onboard image preprocessing for optical images on FPGAs.…”
Section: Introductionmentioning
confidence: 99%